THE HARMONIZATION OF SUNDA ISLAMIC VALUES IN THE SEREN TAUN TRADITION IN KAMPUNG ADAT KASEPUHAN CIPTAGELAR - Ade Priangani; Kunkunrat Kunkunrat; Iwan Gunawan (Lembaga Penelitian Universitas Pasundan, 2022)
The Seren Taun ceremony is a manifestation of the harmony between Islamic religious values ​​and Sundanese culture which is practiced by the people of the Kasepuhan Ciptagelar Traditional Village. Seren Taun means the handover of the past year to the next year as its successor. In the context of the traditional life of the Sundanese cultivators, seren taun is a means to give thanks to God Almighty for all the agricultural products carried out this year, while hoping that their agricultural output will increase in the coming year. More specifically, the seren taun ceremony is an event for handing over crops in the form of rice produced within a year to be stored in the barn or in Sundanese called leuit. Seren Taun is the highlight of all Kasepuhan community activities, such as: Ngaseuk Ceremony, Rice Planting Thanksgiving/Sapang Jadian Pare Ceremony, Thanksgiving Ngidam, Mapag Pare Beukah, Sawenan Ceremony, Thanksgiving Mipit Pare, Nganjaran/Ngaunjuk, Ponggokan. All of these are a series of forms of gratitude for the Ciptagelar community who are Muslim and are manifested in the form of culture.